Silent Corticotroph and Somatotroph Double Pituitary Adenoma: A Case Report and Review of Literature - Isabella L. Pecorari; Lakshmi Priyanka Mahali; Abigail Funari; Roger Fecher; Nisha Suda; Vijay Agarwal (Journal of Neurological Surgery Reports, 2022)
Clinically silent double pituitary adenomas consisting of corticotroph and somatotroph cells are an exceedingly rare clinical finding. In this report, we present the case of a 28-year-old man with a 1-year history of recurrent headaches. Imaging revealed a 2.1 (anterior-posterior) × 2.2 (transverse) × 1.3 (craniocaudal) cm pituitary adenoma invading into the left cavernous sinus and encasing the left internal carotid artery. Endoscopic transnasal resection was performed without complications. Immunohistochemical staining revealed a double adenoma consisting of distinct sparsely granulated somatotroph and densely granulated corticotroph cells that were positive for growth hormone and adrenocorticotropic hormone, respectively. Ki-67 index labeling revealed a level of 6% within the corticotroph adenoma. No increase in serum growth hormone or adrenocorticotropic hormone was found, indicating a clinically silent double adenoma. While transsphenoidal surgery remains a first-line approach for silent adenomas presenting with mass effects, increased rates of proliferative markers, such as the Ki-67 index, provide useful insight into the clinical course of such tumors. Determining the Ki-67 index of silent pituitary adenomas could be valuable in predicting recurrence after initial surgical resection and identifying tumors that are at an increased risk of needing additional therapeutic interventions or more frequent surveillance imaging.